Plasmon-mediated discrete diffraction behaviour of an array of responsive waveguides. Issue 38 (25th September 2019) - Pezzi, Luigia; De Sio, Luciano; Veltri, Alessandro; Cunningham, Alastair; De Luca, Antonio; Büergi, Thomas; Umeton, Cesare; Caputo, Roberto
Abstract : We investigate the discrete diffraction phenomenon in a Polymer-Liquid Crystal-Polymer Slices (POLICRYPS) overlaying a random distribution of gold nanoparticles (AuNPs, plasmonic elements). Abstract : We investigate the discrete diffraction phenomenon in a Polymer-Liquid Crystal-Polymer Slices (POLICRYPS) overlaying a random distribution of gold nanoparticles (AuNPs, plasmonic elements). We study the propagation of a CW green laser beam through the waveguide structure as a function of beam polarization, laser intensity and sample temperature. It turns out that the plasmonic field created at the interface between AuNPs and POLICRYPS waveguides enables and stabilizes the optical field propagation within the responsive nematic liquid crystal channels. The active role of the liquid crystal is pointed out by a polarization, temperature and beam divergence experimental analysis and evidenced by a peculiar trumpet-shaped discrete diffraction pattern. Theoretical simulations confirm that the observed optical behavior is governed by the interaction of the nematic liquid crystal with optical and plasmonic fields.